Growing food and access, education and opportunity through collaboration and dedication to hope - Alicia Ellingsworth; Jennifer Thomas; Lydia Nebell (Urban Food Systems Symposium, 2022)
KC Farm School at Gibbs Road generates an inspiring environment transforming Wyandotte County through community-wide, multi-generational, and participatory food projects while providing vocational training, job opportunities, healing and fun. KC Farm School celebrates our county’s rich cultural heritage, and we offer hope in these urgent times. Our neighbors struggle with food insecurity, economic hardship, limited land access, climate change, soil degradation, disease, and disconnectedness. Many use SNAP benefits, live below the federal poverty level and face food insecurity. Wyandotte County, considered a ‘sacrifice zone’, is home to the country’s third largest rail yard and suffers environmental degradation due to that industry, to silver and limestone mining, and because of aging infrastructure. Still, KC Farm School grows hope by offering education, access, and opportunity to create solutions by working ‘with’ our neighbors not simply ‘for’ them. We learn what our neighbors want by hosting quarterly roundtables. ‘Let’s Grow Wyandotte!’ grew from concerns about food insecurity; and today 300+ households engage in the program which provides plants, seeds, supplies, and mentorship empowering participants to grow their own food. Through relationships with school districts, we bring students on-farm hands-on for farm activities and a robust curriculum, and we offer farm apprenticeships for youth aged 13-18. We collaborate with farmers through the KC Food Hub, Great Plains Regeneration, the KC Young Farmers Chapter of the National Young Farmers Coalition, and Growing Growers Kansas City to address soil health through regenerative practices. We’ve created an economic model that provides opportunities for young farmers and emerging entrepreneurs while increasing food access for our community by hosting a weekly, on-farm farmers market; accepting SNAP, matching with Double-Up Food Bucks, encouraging pay-what-you’re-able, and barter agreements to ensure our neighbors have equitable access to nutritious food and education to lead healthy, whole lives. This win/win/win economic model provides our food and education programming at a rate that is determined by the individual participating; some pay less, and some pay more. In three years, KC Farm School has engaged 30,000+ individuals through participatory food projects, on-farm education and vocational opportunities. On fourteen urban acres, we’re creating innovative solutions with our community as we prove that when we all share what we have, we all have what we need. In this space of hope amid despair, good grows.
Keywords: urban farming; nonprofit; community; workforce development; equity